Representation of a Rebellious Woman of Nepali Society in Sheeba Shah’s Facing My Phantoms - Karki, Data Ram (KMC Research Journal, 2020)
A normalized female self is predefined in society and the society has preconceived image which defines role and position in general. The study outlines a female picture which is beyond unlike societal explanation in Sheeba Shah's Facing My Phantoms in which a female character embodies and represents an image of Nepali woman in Nepalese society. The bold, fearless and daring character is beyond from patriarchal imagination. The portrayed woman character, Sanjeevani is symbolic and representative of rebellious self. Her struggle is for sake of individuality and self in male oriented society. Her voice is strong enough to create and establish own female self-identity in society. The novel advocates a voice of daring woman within a short time frame of Nepali history during civil war. The rebellious picture of Sanjeevani is a futuristic in the contemporary society.